Fear of Missing out in Cryptocurrency Investing - Budi Suryawan, I Putu Gede (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Investment is a driving factor for a country's economic development. One form of investment that is often used is bitcoin investment. This type of investment is an investment alternative that is easily accessible to the wider community. This study aims to find out whether the causes of many cryptocurrency investors are FOMO. This study uses a qualitative research design with a case study approach. Cryptocurrency investments made by new informants are in the trial and error stage so the money invested is not large, only in the hundreds of thousands to millions. The nominal is not that big but it means a lot if it's not used properly. The cause of FOMO among novice investors in investing in cryptocurrency is that many investors have already invested so they want to participate in these investment activities.